Determinants of divestiture choice in South Africa - Siame, Davy (Department of Finance and Tax, 2020)
This research report investigates the determinants of divestiture choice in South Africa. In addition, it examines how the determinants are influenced by the period studied. There are three periods of interest, being the full sample period, the prefinancial crisis period and the post financial crisis period. The determinants of divestiture choice have not been investigated from a South African perspective by prior studies. This report therefore contributes to the literature by exploring a new context. The South African context is unique because of differing laws and regulations as well as socio-economic factors specific to countries in developing markets. This report makes a further contribution by updating the literature on determinants of divestiture choice as post financial crisis data is included in the data set. The research is based on a sample of 102 divestiture transactions (78 spin-offs and 24 sell-offs) over the period 1998 to 2017. Logistic regression is used to ascertain the determinants of divestiture choice using pre-divestiture data of the parent company. The results show that financial performance as measured by return on equity (ROE) and liquidity as measured by the current ratio are significant determinants of divestiture choice over the full sample period (1998 to 2017). The higher the firm’s financial performance, the higher the likelihood of divestiture through spin-off. Contrary to expectation, it was found that the higher the liquidity of the firm, the higher the likelihood of divestiture through sell-off. Financial distress, director ownership, Broad Based Black Economic Empowerment (BBBEE) and effective taxation rates are not found to be significant factors in determining divestiture choice over the entire period of study. Financial performance is found to be a significant determinant of divestiture choice over the pre-financial crisis period (1998 to 2006). The results for this period show that the higher the firm’s financial performance, the higher the likelihood of divestiture through spin-off. The remaining factors are not found to be significant for the prefinancial crisis period. No factors were found to be significant over the post financial crisis period (2009 to 2017). These findings imply that determinants of divestiture choice are not uniform for South Africa and the United States; nor for differing time periods in the South African context. This implies that divestiture determinants vary depending on the context and the economic cycle studied.